AN EXPERIMENTAL DESIGN TO EXERCISE NEGOTIATION IN REQUIREMENTS ENGINEERING - Ahmad, S.; Muda, N. A. (2011)
A framework design is critical to the deployment of empirical investigation. Safety measures must be taken in order to ensure that the data obtained from the study is reliable and the measures taken are valid. This paper provides a framework design to deploy an empirical investigation to assess the effectiveness of negotiation in requirements engineering. It also elaborates the relevance of negotiation in requirements engineering process and its effectiveness. The underlying concept and the motivation which influenced the framework design are stated. The framework design which is divided into population and participants, the experimental process, and methods to minimize bias is thoroughly explained.